THE CONCEPTUAL AND HISTORICAL CONTEXT OF DANISH ARTIST JOHANNES WIEDEWELT - Juhl, Carsten (The Nordic Journal of Aesthetics, 2022)
Review of ELSE MARIE BUKDAHL, JOHANNES WIEDEWELT – TRADITION OG NYBRUD [JOHANNES WIEDEWELT – TRADITION AND BREAKTHROUGH] COPENHAGEN: U PRESS, 2021. 148 PAGES ISBN: 9788793890121